Development and sensory test of eel cookies for pregnant women with chronic energy deficiency using many facet Rasch model: a preliminary study - Sunjaya, Deni Kurniadi; Herawati, Dewi Marhaeni Diah; Puteri, Devi Pratiktowati; Sumintono, Bambang (Progress in Nutrition, 2021)
Study objectives:This study aimed to assessment the respond of pregnant women with chronic energy deficiency on eel cookies. Methods:The study was conducted in three stages. First, a functional food formula based on Anguilla bicolorwas created.Second, the qualities of the food products were examined. Lastly, a sensory assessment was performed with 30 pregnant women. The sensory assessment data were analyzed using many-facet rasch model. Results:Three cookies formulae were made. Among the parameters for the sensory assessment with the consumers, texture was the most difficult criterion to be fulfilled (1.13 logit), followed by taste (0.18 logit), aroma (-0.34 logit), and color (-0.97 logit). The peanut-flavored cookie (0.62 logit) was preferred over cheese or chocolate-flavored. Conclusion:Cookies made from fish bone flour of Anguilla bicolorand local corn may be a better functional food option for addressing chronic energy deficiency in pregnant women.